2015
DOI: 10.1038/jes.2015.41
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal prediction of fine particulate matter using high-resolution satellite images in the Southeastern US 2003–2011

Abstract: Numerous studies have demonstrated that fine particulate matter (PM2.5, particles smaller than 2.5 μm in aerodynamic diameter) is associated with adverse health outcomes. The use of ground monitoring stations of PM2.5 to assess personal exposure; however, induces measurement error. Land use regression provides spatially resolved predictions but land use terms do not vary temporally. Meanwhile, the advent of satellite-retrieved aerosol optical depth (AOD) products have made possible to predict the spatial and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 21 publications
(18 reference statements)
1
72
0
Order By: Relevance
“…The results are in line with other recent studies [52][53][54], which all indicated that land use information such as NDVI can help to predict the PM 2.5 concentration.…”
Section: Model Validationsupporting
confidence: 92%
“…The results are in line with other recent studies [52][53][54], which all indicated that land use information such as NDVI can help to predict the PM 2.5 concentration.…”
Section: Model Validationsupporting
confidence: 92%
“…Included studies showed that R 2 value of MEM was higher than those of the other three models in the same area [17,87,104,136]. Moreover, MAIAC algorithms, which led to a highly accurate of AOD, were mostly used in MEM, significantly improving the R 2 value of the model [7,35,83,120,135]. On the global scale, CTM has been proven to be efficient for the mechanism of completing the prediction from using partial AOD data by AOD component analysis [57]; (2) Adjusting factors: The number of these factors has increased due to the development of prediction models.…”
Section: Discussionmentioning
confidence: 99%
“…In recognition of regional geographical differences, Lee et al [7] predicted PM 2.5 concentrations using IPW in seven southeastern states of the United States in 2016, and they obtained three coefficients of determination (0.770, 0.810, and 0.700) from three different geographical area types. They suggested that their PM 2.5 estimation methods could be applied from urban areas to rural areas.…”
Section: Theory Background and Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Remote-sensing estimates have been used to assess associations between PM 2.5 and cardiovascular disease in epidemiological studies (12,14,17). Some studies have recently used 1-km estimates of PM 2.5 for the United States, which increase their utility for exposomics studies (55,101). Remote-sensing techniques have also been used to estimate an expanding list of environmental exposures, including nitrogen dioxide (NO 2 ) concentrations (35), green spaces (2, 70), temperature (19), the built environment (13,95), outdoor light at night (45), agricultural chemical exposure (60), land cover classifications (11), river plumes (3), water quality (26), and marine microorganisms (39), for example.…”
Section: Infectious Agents/vectorsmentioning
confidence: 99%